Development of standard samples-simulators of weight fraction of acetone insoluble substances in rapeseed lecithins - O. S. Agafonov; E. V. Lisovaya; S. M. Prudnikov; E. P. Victorova (Новые технологии)
Currently, there is an increase in the volume of rapeseed processing, which leads to a natural increase in the production of by-products such as rapeseed lecithin. One of the indicators of the quality of lecithins, which determines the content of physiologically valuable components – phospholipids is the weight fraction of substances insoluble in acetone. The aim of the study is to develop an integrated system for metrological support of an instrumental method for determining the weight fraction of substances insoluble in acetone, contained in rapeseed lecithins, using the pulse NMR method. The main element of this system is standard imitating samples with known metrological values of the mass fraction of substances insoluble in acetone. As a result of the conducted studies of NMR characteristics of natural samples of rapeseed lecithins with different mass fractions of substances insoluble in acetone, the optimal parameters of NM relaxation characteristics of standard imitating samples have been determined. It has been shown that three substances are required to create standard imitating samples, while to simulate the protons contained in the oil phase of rapeseed lecithins two substances are required using spin-spin relaxation time from 77 to 110 ms and a spin-spin relaxation time from 23 to 28 ms, and to imitate phospholipid protons – a substance with a spin-spin relaxation time from 2 to 6 ms is required. On the basis of the study of NMR characteristics of protons contained in samples of chemically inert organic silicon liquids and natural latex, a composition of 6 standard samples-imitators of the mass fraction of substances insoluble in acetone contained in rapeseed lecithins, and a procedure for their use for NMR calibration analyzer AMV-1006 M have been developed.